The Structure and Heat Dependence of Silicon Spreading Resistance Temperature Sensors - Gy. Pásztor; J. Berkecz; N. M. Ficza (Active and Passive Electronic Components)
The construction method of the sensor SRTS with two roundshaped diffusion layers is given. The effect of geometry on the sensor resistance is determined theoretically. An approximating method is given to determine the temperature dependence of the sensor in the range of 200K < T < 400K. Calculated results are compared to measurements.